2020
DOI: 10.1371/journal.pone.0233735
|View full text |Cite
|
Sign up to set email alerts
|

Stability and applicability of the leaf value model for variable nitrogen application based on SPAD value in rice

Abstract: Many fertilization models have been created to scientifically determine the amount of fertilization. With the same purpose, we constructed a nitrogen (N) application model, the leaf value model, which can make N fertilizer decisions in a timely, fast and nondestructive manner during rice planting. However, only one area (A 1 , Jiuzhou Town, Xixiu District, Guizhou Province) and one cultivar (Qyou6) were involved in the construction of the leaf value model. Its stability and applicability could not be well eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
3
7
0
Order By: Relevance
“…Our results showed that grain yield progressively increased with nitrogen fertilization in both cultivars, although in Y21 the yield difference between N 120 and N 180 was not statistically significant (Table 1). The underperformance of Y21 with high nitrogen fertilization is in concordance with its low nitrogen efficiency as compared to other rice cultivars, as has been previously reported by Li et al [36], and demonstrated further by comparing the nitrogen use efficiency of the two cultivars in this study. Both cultivars performed better at moderate (P 90 ) than at high (P 120 ) phosphorus fertilization (Table 1).…”
Section: Yield and Yield-related Parameters And Correlation Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…Our results showed that grain yield progressively increased with nitrogen fertilization in both cultivars, although in Y21 the yield difference between N 120 and N 180 was not statistically significant (Table 1). The underperformance of Y21 with high nitrogen fertilization is in concordance with its low nitrogen efficiency as compared to other rice cultivars, as has been previously reported by Li et al [36], and demonstrated further by comparing the nitrogen use efficiency of the two cultivars in this study. Both cultivars performed better at moderate (P 90 ) than at high (P 120 ) phosphorus fertilization (Table 1).…”
Section: Yield and Yield-related Parameters And Correlation Analysissupporting
confidence: 91%
“…This work represents a comparative analysis of the effects of high, moderate, low-dosage application and non-application of nitrogen and phosphorus fertilizer on the growth, yield, yield-related traits and expression of selected genes in two Chinese hybrid rice cultivars. The cultivar Deyou4727 (herein shortened to D47) has been previously described as drought-tolerant, with a particularly well-developed root system [35], while Yixiangyou2115 (referred to as Y21) was reported as relatively nitrogen-inefficient compared to other hybrid rice cultivars and restorer lines [36].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, some scholars proposed the soil and plant analysis development (SPAD) method for nondestructive rapid measurements of the LCC values of leaves by means of light and electricity [10,11]; furthermore, the relative contents of ChlorophyII obtained by Soil and Plant Analyzer Development 502 (SPAD 502) are highly consistent with the results obtained by chemical experiments, supporting the idea of using this approach instead of the traditional chemical measurement method [12]. However, the drawbacks of this method include limited measuring points and unsuitability for measurement involving a large area [13,14].…”
Section: Introductionsupporting
confidence: 54%
“…Leaf chlorophyll content and nitrogen content are two very important indices of rice nutrition and growth status. Real-time and accurate monitoring of chlorophyll content and nitrogen status of crops is of great signi cance to scienti c cultivation of crops, accurate management of eld fertilizers, and improvement of crop yield and quality [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%